Central European precipitation and temperature extremes in relation to large-scale atmospheric circulation types - Jucundus Jacobeit; Joachim Rathmann; Aandreas Philipp; Philip D. Jones (Meteorologische Zeitschrift, 2009)
There is increasing concern that precipitation and temperature extremes may be changing in frequency and character as a result of changing climate, and the latter is mostly linked with particular changes in the atmospheric circulation. Therefore the question arises - a key question in the climate change prospective - as to how precipitation and temperature extremes are related to large-scale atmospheric circulation types? To study such relationships over an extended period of more than one and a half centuries, we include daily precipitation and temperature time series compiled during the EU project EMULATE (European and North Atlantic daily to multidecadal climate variability) back to 1850 as well as daily mean SLP reconstructions from the same project for the same period. The latter data set has been used for classifying daily circulation types for each season using a simulated annealing clustering technique. Comparing each of these circulation types with their percentages among extreme days and among non-extreme days (with respect to precipitation or temperature) clearly reveals that in most cases only a few of the seasonal circulation types are conducive to the occurrence of daily extremes. This is shown for heavy precipitation and positive temperature extremes (beyond the 98th percentile in each case), related to the winter (DJF) and summer (JJA) seasons for a central European region. Different circulation patterns proved to be important in this context. Thus, in contrast to positive temperature extremes during winter being linked preferably to zonal circulation patterns (positive mode of the North Atlantic Oscillation, NAO), heavy winter precipitation in central Europe is distinctly associated with less zonal patterns characterized by an eastward or southeastward shift of the subpolar centre of low pressure implying only weak correlations with the NAO. Furthermore, particular indices reveal that changing frequencies of extremes are not only due to corresponding frequency changes of these conducive circulation types, but also to changes of their association to precipitation or temperature extremes (reflected by changes in the percentage of extremes related to the overall occurrence of the corresponding circulation type). These within-type changes of circulation types often govern the low-frequency variations in the overall incidence of extremes.